The investigation of the relationship between citizen participation and organizational citizenship behavior in the Gachsaran’s municipality - kamran, Jalal; Ariyan, Fahimeh; Amini, Ehsan; Zafari, Masood (Ciência e Natura, 2015)
This study has tried to examine the relationship between two variables as citizen participation and organizational citizenship behavior in the Gachsaran’s municipality. Participation is of urban life’s requirements and it is realized when the burgher has converted from individual life and with a sense of collective responsibility to citizens. In order to meet the needs of urban development and advertence to the posterity’s share, therefore, we should plan the administration of the urban life’s affair on the basis of a systematic pattern of planning with the meaningful, informed and voluntary participation of citizens.